Reconstructing Productive Rahn Tasjily Financing with Wakalah Tabarru’: A Maqasid-Based Approach for Agricultural Risk Mitigation in Islamic Microfinance - Nur Irmandi; Cucu Susilawati; Sofian Al Hakim; Syamsurijal Syamsurijal; Elpha Senia Agustina (STAI Al-Mas'udiyah, 2026)
The agricultural sector faces a financing paradox: farmers possess high-value assets (land) that are illiquid under conventional collateral schemes, leading to financial exclusion. Previous studies on Rahn Tasjily primarily focus on legal permissibility and collateral flexibility, yet they often neglect the integration of social contracts as a risk mitigation mechanism for high-risk agricultural financing. This study aims to fill this gap by proposing a hybrid financing model that integrates commercial contracts (Rahn Tasjily, Qardh, Ijarah) with a social contract (Wakalah Tabarru’). Using a qualitative-conceptual approach with a Maqasid al-Shari’ah framework, this study constructs a model where Baitut Tamwil provides liquidity while Baitul Maal acts as a risk mitigator through technical assistance. The results demonstrate that this hybrid model resolves the liquidity trap for farmers without asset dispossession and mitigates default risk through structured tabarru’-based supervision. This study contributes to the literature on Islamic microfinance by offering a concrete model of synergy between commercial and social functions in BMT operations.